ADACTIVE STRATEGY OF PANGLIMA LAOT INSTITUTION IN SUSTAINABLE COASTAL AREA MANAGEMENT IN THE PROVINCE OF ACEH-INDONESIA - Eva Wardah; Agussabti; Indra Indra; Yanis Rinaldi (CV. RADJA PUBLIKA, 2025)
The Panglima Laot institution plays a pivotal role in the sustainable management of Aceh's coastal regions by leveraging traditional practices and local wisdom. However, increasing pressures from climate change, economic modernization, and declining fish stocks necessitate adaptive strategies to ensure its continued effectiveness. This study investigates the adaptive strategies employed by Panglima Laot, focusing on integrating traditional governance with modern innovations to address environmental and social challenges. Utilizing a SWOT analysis framework, the study identifies the institution's strengths, weaknesses, opportunities, and threats. Key findings highlight the need for enhancing institutional capacity, documenting traditional knowledge, and fostering collaborations with governmental and international organizations. By leveraging its cultural significance and community trust, Panglima Laot can integrate modern technologies, such as GIS, to improve resource management while maintaining traditional values. These strategies are critical to strengthening the institution’s role in promoting equitable and sustainable coastal resource management. The study concludes with actionable recommendations for policy enhancement, community engagement, and capacity building to support Panglima Laot in navigating the evolving complexities of coastal management in Aceh.